Transport analysis of an Air Gap Membrane Distillation (AGMD) process - Hawlader, Mohammad Nurul Alam; Bahar, Rubina; Ng, K. C.; Loh, Jian Wei Stanley (2011)
Membrane distillation (MD) desalination is an emerging technology for fresh water production. This process incorporates phase change and transport of vapour through a hydrophobic membrane due to difference in vapour pressure across the membrane. The results from experimental studies and the 1 dimensional transport analyses of the heat and mass transfer processes on an air gap MD (AGMD) unit are presented in this paper. The effects of different operating variables including feed and coolant temperatures, air gap, membrane support mesh size, feed concentration and feed and coolant flow rates were investigated. Mass transport through membrane, membrane support, air gap and condensation on the coolant plate has been analysed and expression for global mass transfer coefficient has been derived. The maximum distillate flux achieved was 5.11 kg/m2hr at a feed temperature of 60oC, coolant temperature of 10oC and an air gap of 2.5 mm. Per kW of energy input a 2.32 kg/m2hr flux was obtained. Feed temperature and air gap width were found to have significant influence on the performance of the membranes.